Pain-Specific Resilience in People Living With HIV and Chronic Pain: Beneficial Associations With Coping Strategies and Catastrophizing - Gonzalez, Cesar E. (Front Psychol, 2019)
OBJECTIVE: Chronic pain is increasingly recognized as a common and disabling problem for people living with HIV (PLWH). In a recent systematic review of psychosocial factors associated with chronic pain in PLWH, it was reported that very few studies to date have examined protective psychological factors that might help mitigate chronic pain for PLWH. The current study examined pain-specific resilience in relation to clinical and experimental pain, as well as pain coping in PLWH and chronic pain. Pain-specific resilience specifically refers to the ability to maintain relatively stable, healthy levels of psychological and physical functioning in the face of ongoing and persistent pain. METHODS: A total of 85 PLWH (mean CD4 = 643; 13% detectable viral load ≥200; 99% on antiretroviral therapy) who met criteria for chronic pain (>3 consecutive month’s duration) were enrolled. Medical records were reviewed to confirm clinical data. All participants provided sociodemographic information prior to completing the following validated measures: Pain Resilience Scale (PRS), Coping Strategies Questionnaire-Revised (CSQ-R), Center for Epidemiologic Studies – Depression Scale (CES-D), and the Brief Pain Inventory – Short Form (BPI-SF). They then completed a quantitative sensory testing battery designed to assess tolerance for painful heat and cold stimuli. RESULTS: In adjusted multiple regression models controlling for covariates, greater pain-specific resilience was significantly associated with less pain interference (p = 0.022) on the BPI-SF, less pain catastrophizing (p = 0.002), greater use of distraction (p = 0.027) and coping self-statements (p = 0.039) on the CSQ-R, as well as significantly greater heat pain tolerance (p = 0.009). Finally, results of a parallel multiple mediation model demonstrated that the effect of pain-specific resilience on heat pain tolerance was indirectly transmitted through less pain catastrophizing (95% confidence interval:0.0042 to 0.0354), but not use of distraction (95% confidence interval: −0.0140 to 0.0137) or coping self-statements (95% confidence interval: −0.0075 to 0.0255). CONCLUSION: The findings suggest that pain-specific resilience may promote adaptation and positive coping in PLWH and chronic pain.